Undertreating pain violates ethical principles. Issue 10 (30th September 2009) - Macpherson, C
Abstract : Disabling pain or symptoms can occur at any age from many different causes. Pain and palliative specialists are able to relieve most pain and symptoms, although repeated adjustments to modalities, medications and doses may be needed. Because pain and palliative specialists comprise only a small percentage of physicians, many patients find it difficult to access them or obtain pain relief. Globally, there are too few such specialists to meet existing needs. Most are affiliated with hospice and palliative units, so their accessibility to patients without terminal conditions is negligible. Doctors outside pain and palliative specialties are often unfamiliar with pain guidelines and sceptical about patient reports of unrelieved pain. They are therefore likely to undertreat it. Undertreating pain, however, violates respect for persons and beneficence. This paper reviews literature supporting these claims and offers a narrative description of the author's attempts to find relief from shingles and postherpetic neuralgia. It argues that physicians in most specialties are not, but should be, familiar with palliative evidence and guidelines so that they are equipped to relieve pain and symptoms quickly and effectively. Such information should be routinely introduced in medical curricula to encourage the mastery of knowledge, attitudes and skills necessary to upholding ethical principles and to ensure that more doctors in any discipline are willing to believe and be compassionate to patients whose pain is unresponsive to initial treatments. Routinely exposing students to such information would better prepare them to fulfil their professional duties to patients and society.